(untitled) (Docentes 2.0 Journal, 2022)
The present documentary research was supported by the qualitative approach, of the hermeneutical paradigm, of an informative-interpretative type, with a topic design. Currently, the topic of education is of great importance; many times, negative and positive criticisms are heard in the same way because, in the country, there is a specific deficiency in terms of education, for which it is considered a problem both for public policies and private. Nowadays, it is observed that the responsibility of educating our students falls on the two essential pillars in the life of the student body, the family and the school. In the family context, parents carry out educational and social tasks; the teacher is the crucial educational training agent in school. For this reason, this essay aims to analyze the situation of teachers, the functions currently performed, and if they are appropriate for the student community. It is essential to mention that teachers not only transmit knowledge but also influence student decisions, promoting the values that young people will take directly or indirectly in their training before society. In this way, it is of the utmost importance to pay special attention to the different factors contributing to the teacher’s performance during the student’s development.